Initial Environmental Examination (IEE) Guideline for Health Sectors in Nepal - Aryal, J (Journal of Nepal Health Research Council, 2013)
Sustainable environmental management is of great concern due to rapidly growing number of health care institutions in Nepal. It is mandatory to regulate and develop a practice for impact assessment due to establishment and operation of health care facilities of Nepal through user’s friendly procedure. This study was carried out to review Initial Environmental Examination (IEE) process and to recommend appropriate IEE study guideline for establishment and operation of health care facilities in Nepal. Primary data were collected through consultation and interaction with domain experts and concerned stakeholders. Secondary sources of information include review of available literature, browsing information from internet, review of IEE studies of developmental projects of different sectors. Review of IEE documents showed that potential effects of the health care projects on environment are inadequately mentioned and whenever mentioned not applied in operational stages. A clear and user’s friendly IEE guideline for establishment and operation health care facilities has been proposed to conduct IEE study in Nepal. Keywords: Initial Environmental Examination; IEE process; Health Sector.